Pengaruh Electronic Word Of Mouth, Celebrity Endorser, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Somethinc - Astri Sari Firdausa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Currently skin and body care products are one of the important needs for the community because they are used to support their appearance to make them look more attractive. This also encourages the growth of the body care industry, for example cosmetics in Indonesia. One of the brands that is being liked by the public is SomeThinc. Something that managed to enter the ranks of the top 50 Indonesian brands. This study aims to determine the effect of electronic word of mouth (e-wom), celebrity endorser, and product quality variables on purchasing decisions for Somethinc products. Research data is primary data derived from questionnaires and secondary data. The sampling method used is non-probability sampling. Collecting data using google form and the sample in this study were 360 respondents who were consumers of Somethinc products. The analytical method used in this research is multiple linear regression. The results of this study indicate that the variable electronic word of mouth has a positive effect on purchasing decisions, celebrity endorsers have a positive effect on purchasing decisions, and product quality has a positive effect on purchasing decisions.